A multi-strip multi-gap RPC barrel for time-of-flight measurements - Kiš, Mladen; Ciobanu, Mircea; Deppner, Ingo Martin; Hildenbrand, K. D.; Herrmann, Norbert; Kang, T. I.; Kim, Y. J.; Koczon, P.; Leifels, Y.; Marquardt, M.; Petrovici, M.; Piasecki, Krzysztof; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2011)
The FOPI detector [1] at the heavy-ion synchrotron SIS-18 at GSI in Darmstadt has upgraded part of its time-of-flight (ToF) system by adding a new sub-detector shell (called the MMRPC Barrel) that is made out of Multi-strip Multi-gap Resistive-Plate Counters (MMRPCs). The MMRPC Barrel has an active area of 5m2 covered by 2400 individual anode strips [2], [3] which are read out at both ends by custom-designed electronics [4], [5]. With these multi-strip anodes we have obtained an enhanced detector granularity with 95% efficiency and a ToF resolution σToF better than 90ps which increases the identification limit for charged kaons up to laboratory momenta of at least 1GeV/c. In this paper we report on the design, construction and operational characteristics of the MMRPC Barrel and describe its performance during the first experiments.